Financial Sector Crisis and Restructuring : Lessons from Asia: Lessons from Asia - Teo, Leslie (Occasional Papers; Occasional Paper ;, 2000)
This paper reviews the policy responses of Indonesia, Korea, and Thailand to the Asian crisis that erupted in 1997 and compares the actions of these three countries with those of Malaysia and the Philippines, which were buffeted by the crisis. Although work is still under way in all the affected countries, and thus any judgements are necessarily tentative, important lessons can be learned from the various experience of the last two years.